En bloc resection of primary tumors of the thoracic spine: indications, planning, morbidity. (June 2014) - Boriani, Stefano; Bandiera, Stefano; Colangeli, Simone; Ghermandi, Riccardo; Gasbarrini, Alessandro
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: We aimed to describe surgical planning, technique, and complications of en bloc resection in the thoracic spine in patients who opted for surgery with en bloc resection and a tumor-free margin. Methods: Oncologic and functional results were recorded for 134 patients (53% male, age 44 ± 18 years) who had undergone en bloc resection for primary tumors (90 cases) and bone metastases (44 cases). Patients were followed until death or the latest follow-up examination (0–211 months, median 47 months). Surgeries were performed from 1990 to 2007 by the same team. An ongoing critical analysis of local control rates, surgical complications, and expected versus actual loss of function enabled the authors to refine the surgical technique and propose seven different types of resection. Results and Discussion: En bloc resection is a demanding procedure and requires careful planning after a careful decision-making process. The patient has to correctly understand the purpose of the surgery, based on oncological staging, in order to accept or decide against the procedure after weighing the possible morbidity and functional loss against the expected final result. Techniques of En Bloc Resection: Seven different strategies to perform en bloc resection in the thoracic spine, based on four combinations of surgical approaches (anterior, posterior, anterior followed by posterior, and posterior followed by simultaneous anterior and posterior) are identified and proposed. This planning is based on Weinstein–Boriani–Biagini (WBB) surgical staging. The surgical plan was designed to achieve the required oncologic margin with the minimum achievable morbidity.